Direct transfer to angio-suite versus computed tomography-transit in patients receiving mechanical thrombectomy: a randomized trial - Pfaff, Johannes; Schönenberger, Silvia; Herweh, Christian; Ulfert, Christian; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Möhlenbruch, Markus Alfred (Stroke, 2020)
Background and Purpose: To quantify workflow metrics in patients receiving stroke imaging (noncontrast-enhanced computed tomography [CT] and CT-angiography) in either a computed-tomography scanner suite (CT-Transit [CTT]) or an angio-suite (direct transfer to angio-suite—[DTAS]—using flat-panel CT) before undergoing mechanical thrombectomy. Methods: Prospective, single-center investigator initiated randomized controlled trial in a comprehensive stroke center focusing on time from imaging to groin puncture (primary end point) and time from hospital admission to final angiographic result (secondary end point) in patients receiving mechanical thrombectomy for anterior circulation large vessel occlusion after randomization to the CTT or DTAS pathway. Results: The trial was stopped early after the enrollment of n=60 patients (CTT: n=34/60 [56.7 %]; DTAS: n=26/60 [43.3%]) of n=110 planned patients because of a preplanned interim analysis. Time from imaging to groin puncture was shorter in DTAS-patients (in minutes, median [interquartile range]: CTT: 26 [23-32]; DTAS: 19 [15-23]; P value: 0.001). Time from hospital admission to stroke imaging was shorter in patients randomized to DTAS (CTT: 12 (7-18); DTAS: 21 (15-25), P value: 0.007). Time from hospital admission to final angiographic reperfusion was comparable between patient groups (CTT: 78 [58-92], DTAS: 80 [66-118]; P value: 0.067). Conclusions: This trial showed a reduction in time from imaging to groin-puncture when patients are transferred directly to the angiosuite for advanced stroke-imaging compared with imaging in a CT scanner suite. This time saving was outweighed by a longer admission to imaging time and could not translate into a shorter time to final angiographic reperfusion in this trial.
Gesehen am 24.09.2020